Why people should not be poor? - Chandhoke, Neera (2012)
Though much intellectual energy has been expended on the "poverty problem" in India, the debate simply does not take into account the highly unequal social context in which poverty is produced and reproduced. Can we reflect on the right not to be poor without taking on these background inequalities? Arguably, the right not to be poor is best articulated as a subset of the generic right to equality. The concept of equality is, however, not self-explanatory. In many circles, redistributive justice has replaced equality. It is therefore time to ask the question - equality for what? Is equality only about the provision of minimal resources, or is it about enabling a sense of self-worth so that people can participat in the multiple transactions of society with a degree of confidence? Unless we are careful about the way we approach the poverty debate, we will land up not with equality, but with "sufficientarianism". - Reproduced.
Keywords: Poverty